2009
DOI: 10.1038/nature08752
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming towards pluripotency requires AID-dependent DNA demethylation

Abstract: Reprogramming of somatic cell nuclei to yield induced pluripotent stem (iPS) cells makes possible derivation of patient-specific stem cells for regenerative medicine. However, iPS cell generation is asynchronous and slow (2-3 weeks), the frequency is low (, 0.1%), and DNA demethylation constitutes a bottleneck. To determine regulatory mechanisms involved in reprogramming, we generated interspecies heterokaryons (fused mouse embryonic stem (ES) cells and human fibroblasts) that induce reprogramming synchronousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
561
7
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 626 publications
(592 citation statements)
references
References 49 publications
(56 reference statements)
13
561
7
6
Order By: Relevance
“…Typically, reactivation of previously silent genes is detected between 24 and 48 hours after nuclear transplantation 10,11,16,43 . Similar kinetics are observed following mouse ES cell fusion to human lympho cytes 37 or fibroblasts 45 . The oocyte exerts its transcriptional reprogramming activity on a very large scale, not only reactivating pluripotency genes, such as OCT4, SOX2 and NANOG, but also activating, to a certain extent, many different genes that are not actively transcribed in the oocyte 49 .…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Typically, reactivation of previously silent genes is detected between 24 and 48 hours after nuclear transplantation 10,11,16,43 . Similar kinetics are observed following mouse ES cell fusion to human lympho cytes 37 or fibroblasts 45 . The oocyte exerts its transcriptional reprogramming activity on a very large scale, not only reactivating pluripotency genes, such as OCT4, SOX2 and NANOG, but also activating, to a certain extent, many different genes that are not actively transcribed in the oocyte 49 .…”
supporting
confidence: 66%
“…Two examples of enzymes that are thought to play a part in active DNA demethylation are growth arrest and DNA damage-inducible 45α (GADD45α) 42 and activation-induced deaminase (AID) 45 . More recently, in mouse eggs and early embryos, the TET enzymes have been shown to help active DNA demethylation by hydroxylating of methylated cytosine [46][47][48] .…”
Section: Histone and Dna Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report published online in Nature on December 21, 2009, Bhutani et al [1] developed a strategy in which reprogramming was initiated by fusing mouse ESCs with human skin cells to create hybrids called heterokaryons, resulting in astonishingly quick and efficient reprogramming in just 1 day and with extremely high efficiency ($70%). Key advantages of this heterokaryon-based approach included rapid access to the earliest reprogramming events and a more efficient and synchronous environment through which specific pluripotency mechanisms could be uncovered.…”
Section: Heterokaryon-based Reprogramming: Fast Track Toward Pluripotmentioning
confidence: 99%
“…Key advantages of this heterokaryon-based approach included rapid access to the earliest reprogramming events and a more efficient and synchronous environment through which specific pluripotency mechanisms could be uncovered. Moreover, the researchers showed that reprogramming toward pluripotency in single heterokaryons was initiated without cell division or DNA replication [1]. The use of interspecies (between mouse and human) heterokaryons allowed for a distinction of transcripts derived from the two fused cell types, and reprogramming was assessed immediately after fusion without the need for cell division or DNA replication.…”
Section: Heterokaryon-based Reprogramming: Fast Track Toward Pluripotmentioning
confidence: 99%